25-hydroxycholesterol: an integrator of antiviral ability and signaling - Zhang, Jialu; Zhu, Yaohong; Wang, Xiaojia; Wang, Jiufeng (Frontiers in Immunology, 2023)
Cholesterol, as an important component in mammalian cells, is efficient for viral entry, replication, and assembly. Oxysterols especially hydroxylated cholesterols are recognized as novel regulators of the innate immune response. The antiviral ability of 25HC (25-Hydroxycholesterol) is uncovered due to its role as a metabolic product of the interferon-stimulated gene CH25H (cholesterol-25-hydroxylase). With the advancement of research, the biological functions of 25HC and its structural functions have been interpreted gradually. Furthermore, the underlying mechanisms of antiviral effect of 25HC are not only limited to interferon regulation. Taken up by the special biosynthetic ways and structure, 25HC contributes to modulate not only the cholesterol metabolism but also autophagy and inflammation by regulating signaling pathways. The outcome of modulation by 25HC seems to be largely dependent on the cell types, viruses and context of cell microenvironments. In this paper, we review the recent proceedings on the regulatory effect of 25HC on interferon-independent signaling pathways related to its antiviral capacity and its putative underlying mechanisms.